REPRESENTATION OF KOREAN TEENAGERS IN INDONESIAN LITERARY WORKS - YULIAWATI, Dwi Widyaningrum (International Journal of Korean Humanities and Social Sciences, 2017)
It can be said that Korean Wave has triggered the appearance of a new chapter in Indonesian literature works, namely the emergence of literature works related to Korea. Indonesian writes all of these fictions and majority featuring Korean, especially Korean teenagers as the character and use Korea related problems as story theme, setting, etc. This paper is discussing how Korean teenagers represented in Indonesian teenage literature works. Representation is meant here is as the depiction or reflection that symbolizes social reality. Of course, reality reflected in a literary work is not always an actual fact, there is frequent a tendency of reality idealized by the author, in this case is Indonesian author’s idealism. From the examination undertaken on Summer in Seoul and Oppa and I: Love Signs teenage fictions showed the following results. Seen from the perspective of adolescence developmental psychology, Korean teenagers are constructed as figure who have had mature personality, who have achieved emotional, moral, social, and intellectual independence. As a member of a family, Korean adolescent represented as a son, daughter, brother, and sister who do not only take responsibility for themselves but also for others. Then from the perspective of their relation with peers group, they are described as teenagers who have been able to expand their social relationships and have also been able to maintain those relationships. Furthermore, within in the context of education, Korean teenagers are described as young people who have been able to draw up a clear plan for the future.